PERMASALAHAN GENDER DALAM PEMENUHAN HAK ANAK PADA KELUARGA KURANG MAMPU - Sudarto, Yodi; Milyan, Paraswati Daril (SOCIOLOGIE, 2013)
This study examines gender issues in the fulfillment of the rights of children in disadvantaged families. The research approach used in this study is a qualitative approach, while using the method of analysis used descriptive. From the research results obtained illustrate the fact that there are many inaccuracies in the fulfillment of child rights in particular his poor family. Things like this are caused by many things including the limitations of economic and cultural presence menganit patriarchy. Impact resulting from the above override most women, although there are some that hit men. These impacts may include dependency, subordination and hegemony.Keywords: Gender, children, disadvantaged families